Incision and stress regulation in borderline personality disorder: neurobiological mechanisms of self-injurious behaviour - Reitz, Sarah; Kirsch, Peter; Meyer-Lindenberg, Andreas; Treede, Rolf-Detlef; Baumgärtner, Ulf; Bohus, Martin; Schmahl, Christian (The British journal of psychiatry, 2015)
Background: Patients with borderline personality disorder frequently show non-suicidal self-injury (NSSI). In these patients, NSSI often serves to reduce high levels of stress. Aims: Investigation of neurobiological mechanisms of NSSI in borderline personality disorder. Method: In total, 21 women with borderline personality disorder and 17 healthy controls underwent a stress induction, followed by either an incision into the forearm or a sham treatment. Afterwards participants underwent resting-state functional magnetic resonance imaging while aversive tension, heart rate and heart rate variability were assessed. Results: We found a significant influence of incision on subjective and objective stress levels with a stronger decrease of aversive tension in the borderline personality disorder group following incision than sham. Amygdala activity decreased more and functional connectivity with superior frontal gyrus normalised after incision in the borderline personality disorder group. Conclusions: Decreased stress levels and amygdala activity after incision support the assumption of an influence of NSSI on emotion regulation in individuals with borderline personality disorder and aids in understanding why these patients use self-inflicted pain to reduce inner tension.
Gesehen am 19.02.2018